2008
DOI: 10.1111/j.1747-0765.2008.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of NO3interception of the parasitic angiospermOrobanchespp. using a positron-emitting tracer imaging system and13NO3: A new method for the visualization and quantitative analysis of the NO3interception ratio

Abstract: The root parasitic plants Orobanche spp. (broomrapes) seriously affect agricultural production. A visualization and quantitative analytical method for the interception of nutrients was established using a positron-emitting tracer imaging system and 13 NO 3 -. By using this analytical method that involves volume normalization with 18 Fimages, the nitrogen nutrient interception ratio of the Orobanche spp. was calculated to be 73.6 ± 3.9% in a host-parasite system of red clover (Trifolium pratense L.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…While recent work has shown that the xylem-feeding hemiparasite Rhinanthus minor cannot access N fixed by its legume host [15], the situation is less clear in phloem-feeding holoparasites like O. minor , with the assumption being that fixed N must cycle through the xylem to the phloem before being abstracted by the parasite [16]. However, rapid N transfer from a red clover ( Trifolium pratense ) host to O. minor without apparent cycling through the host shoot has been documented [17]. The parasite could abstract a majority of the 13 NO 3 − fed to parasitised roots, while abstraction from non-parasitised roots was negligible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While recent work has shown that the xylem-feeding hemiparasite Rhinanthus minor cannot access N fixed by its legume host [15], the situation is less clear in phloem-feeding holoparasites like O. minor , with the assumption being that fixed N must cycle through the xylem to the phloem before being abstracted by the parasite [16]. However, rapid N transfer from a red clover ( Trifolium pratense ) host to O. minor without apparent cycling through the host shoot has been documented [17]. The parasite could abstract a majority of the 13 NO 3 − fed to parasitised roots, while abstraction from non-parasitised roots was negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Its host, red clover ( Trifolium pratense L.) is a widely used forage crop globally. As such, this pair represents a suitable model system for studies of the host–parasite interaction [17,19]. Given our understanding that holoparasites compete for plant resources, we hypothesised that shifts in host C–N balance would cause changes in the competitive balance in the three-way interaction between host growth, N fixation and the parasite.…”
Section: Introductionmentioning
confidence: 99%
“…Holoparasites depend on their host for carbon and nitrogen resources to grow and develop (Kawachi et al, 2008; Irving and Cameron, 2009). The flow of these resources from the host to the parasite is the limiting factor for holoparasite growth (Hibberd et al, 1998, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…2001) and red clover ( Trifolium pratense L.) with a parasitic plant Orobanche sp. (Kawachi et al. 2008) has been visualized as real‐time images and analyzed with PETIS.…”
Section: Introductionmentioning
confidence: 99%
“…The transport of nitrogen nutrition in rice (Oryza sativa L.) (Kiyomiya et al 2001), soybean (Glycine max L.) (Ohtake et al 2001) and red clover (Trifolium pratense L.) with a parasitic plant Orobanche sp. (Kawachi et al 2008) has been visualized as real-time images and analyzed with PETIS. Quantitative analyses with mathematical models are also applicable to PETIS data.…”
Section: Introductionmentioning
confidence: 99%